If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7+7(7n=9)
We move all terms to the left:
7+7(7n-(9))=0
We multiply parentheses
49n-63+7=0
We add all the numbers together, and all the variables
49n-56=0
We move all terms containing n to the left, all other terms to the right
49n=56
n=56/49
n=1+1/7
| 6p+4(2p+3-p)=2(6+5p)+7 | | 85-2x=-15+3x | | r−3=14.3 | | -7(2y-1)15y=-11 | | -18=-5-(6k-19) | | y+2y=2 | | 3+6s=4(s-12)+19 | | 4x+7=15+0 | | 4x+7=15=0 | | (3x-3=4x+1,x) | | 2x+32/5=5x-4/5 | | 2=-0.01x | | N+3n=188 | | H=8(4b)^2+2 | | 2x+1/4=-3/4x | | (5x+11=x-5,x) | | 10x+23=17x-37 | | X+19=-2x | | 9x=10x+7 | | 5x+11=x-5,x | | (X+4)x=165 | | 18-0.33x=-7 | | 20x-3=17x-36 | | 2/3+n=7/3 | | 6*14=n | | 5(3x+12)-9=6 | | 16w=6+40 | | 16w=16+40 | | 2.1n-531=18 | | x/3+x+20=180 | | y=183 | | -5(w+3)=-5w+1 |